Factor Associated with Incidence of Preeclampsia at Mentawai Islands Regional General Hospital - Idaman, Meldafia; Sitorus, Yeni Campisi Rosmaida BR; Darma, Ika Yulia; Hayu, Ramah; Zaimy, Silvi (International Journal of Multidisciplinary Approach Research and Science, 2024)
The World Health Organization states that the highest complications in pregnancy and childbirth are bleeding with a case number of 32.1%, followed by preeclampsia 26.7% and premature rupture of membranes with an incidence rate of 24.98. The study aimed to determine the factors associated with the incidence of preeclampsia at the Mentawai Islands District General Hospital.This type of research is analytic with a case-control design with a retrospective approach. The population is all mothers giving birth at the Mentawai Islands Hospital in 2022, totaling 279 people. Samples were taken by matching and systematic random sampling of 30 respondents, the data used were secondary data taken from medical records using a checklist. Data were analyzed univariately and bivariate with the chi-square statistical test. The results showed that 15 people had preeclampsia, 8 respondents (53.3%) had a history of hypertension, 5 respondents (33.3%) suffered from obesity, and 4 respondents (26.7%) had diabetes mellitus.the Mentawai Islands District General Hospital, a p-value of 0.020 was obtained, for the relationship between obesity and the incidence of preeclampsia at the Mentawai Islands District General Hospital, a p-value was obtained of 0.014, The Mentawai Islands District General Hospital obtained a p-value of 0.032. In conclusion, there is a relationship between a history of hypertension, obesity, diabetes mellitus, and the incidence of preeclampsia at the Mentawai Islands District General Hospital. Suggestions, it is hoped that health workers can detect preeclampsia early in pregnant women to reduce the incidence of preeclampsia in Indonesia, especially in the Mentawai Islands.